Activation of Nrf2 signaling by Icariin protects against 6‐OHDA‐induced neurotoxicity. (5th April 2019) - Zhu, Li; Li, DaiDi; Chen, Ce; Wang, GuoQing; Shi, JingShan; Zhang, Feng
Abstract: Nerve damage is the main pathogenesis of neurodegenerative diseases. Recently, in search for a promising therapeutic target that could stop neurodegenerative diseases progression, the antioxidant signaling pathway regulated by transcription factor nuclear factor erythroid 2‐related factor 2 (Nrf2) has attracted new hopes. Icariin (ICA) exhibited a battery of pharmacological properties, including antioxidation, anti‐aging, and anti‐inflammation activities. Recent studies indicate ICA conferred neuroprotection against brain ischemic injury and neurodegenerative diseases. However, the mechanisms underlying ICA‐mediated neuroprotection remain unelucidated. This study aimed at analyzing whether ICA evoked neuroprotection against 6‐hydroxydopamine (6‐OHDA)‐induced neurotoxicity in PC12 cells and the mechanisms of action. ICA protected against 6‐OHDA‐induced neuronal damage, accompanied by the inhibition of cell apoptosis through the marked decreases in the Bax/Bcl‐2 ratio, cytochrome c release, and caspase‐3 cleavage. In addition, the activation of Nrf2 signaling pathway was responsible for ICA‐mediated neuroprotection. First, ICA relieved reactive oxygen species accumulation and increased superoxide dismutase generation via the activation of Nrf2 signaling. Second, Nrf2 knockdown by siRNA reversed ICA‐mediated neuroprotection. Together, these results suggested ICA‐mediated neuroprotection might be attributable to the activation of Nrf2 pathway via antioxidative signaling pathways.